2023
DOI: 10.3390/bs14010007
|View full text |Cite
|
Sign up to set email alerts
|

Well-Being, Mental Health, and Study Characteristics of Medical Students before and during the Pandemic

Alexandra Huber,
Luna Rabl,
Thomas Höge-Raisig
et al.

Abstract: Medical students report high demands, stressors, pressure to perform, and a lack of resources, and are therefore at a higher risk for mental strain and burnout. Due to the COVID-19 pandemic, study conditions have changed, and new challenges have emerged. Thus, this study aimed to examine medical students’ well-being, mental health, and study characteristics before and during the pandemic. Data from 988 Austrian medical students were included into the cross-sectional comparisons, and 63 students were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Previous science of science studies of science in general found that the COVID pandemic negatively affected levels of scientific and academic productivity in the science, technology, engineering, and mathematics (STEM) and medicine fields [ 16 , 22 ]. Compared to male scientists, the negative impacts of COVID disproportionately affected female scientists, who were faced with increased caregiving responsibilities to children and other family members.…”
Section: Introductionmentioning
confidence: 99%
“…Previous science of science studies of science in general found that the COVID pandemic negatively affected levels of scientific and academic productivity in the science, technology, engineering, and mathematics (STEM) and medicine fields [ 16 , 22 ]. Compared to male scientists, the negative impacts of COVID disproportionately affected female scientists, who were faced with increased caregiving responsibilities to children and other family members.…”
Section: Introductionmentioning
confidence: 99%